EXTRACTION OF BIOACTIVE CHEMICAL COMPOUNDS AND ANTIBACTERIAL ACTIVITY OF BIOWASTE FRUIT PEELS EXTRACT OF PUNICA GRANATUM - Bankim Chandra Nandy*2Richa Sharma1, Richa Saxena1 (Journal of Biomedical and Pharmaceutical Research, 2017)
Recently, research has gained a renewed focus on herbal products and their biowaste that play an important role in the developing world due to limited modern health service. Various parts of Punica granatum was shown to exhibit antibacterial effects against a wide variety of bacteria. This study conferred the screening of qualitative and quantitative analysis of the major bioactive constituents of biowaste peel extract of Punica granatum with their comparative antibacterial efficacy of ethanolic and methanolic extracts against pathogenic bacteria (Staphylococcus aureus and Proteus vulgaris). The percentage value of yield extraction in ethanolic extract was 55.82 % and methanolic extract was 52.48 %. The total phenolic content was 337 ± 0.012 and 329 ± 0.02 mg/g of dry weight of ethanolic and methanolic extracts, respectively, expressed as gallic acid equivalents. The total flavonoid content was 197 ± 0.032 and 193 ± 0.061 mg/g for ethanolic and methanolic extracts, respectively, expressed as quercetin equivalents. Hence, it could be pursued further for obtaining phytomedicine. The results showed that the crude ethanolic extract has highest activity then methanolic extract. These observations could be the basis for the usefulness of ethanolic extract of the biowaste fruit peels of Punica granatum in the treatment remedies for microbial infections. Keywords: Herbal medicines, bioactive compounds, extract Punica granatum